2023
DOI: 10.1097/hc9.0000000000000224
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral weight-loss interventions for patients with NAFLD: A systematic scoping review

Abstract: Background: Clinically significant weight loss—which requires sustained dietary and physical activity changes—is central to treating NAFLD. Although behavioral interventions have demonstrated effectiveness in promoting weight loss among primary prevention populations, the data are limited among patients with NAFLD who need weight loss for treatment. We undertook this scoping review to map the existing data on the characteristics, weight-loss outcomes, and determinants of success of interventions ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
0
1
0
Order By: Relevance
“…Successful interventions for weight loss in MASLD incorporate behavioral interventions such as teaching self-monitoring skills and promoting behavioral self-awareness, goal-setting, and problem-solving. Trials have demonstrated that taking behavioral theory into account, particularly social cognitive theory (self-monitoring and self-efficacy as key concepts) and CBT, leads to increased success in lifestyle modification interventions 15 …”
Section: Masldmentioning
confidence: 99%
See 1 more Smart Citation
“…Successful interventions for weight loss in MASLD incorporate behavioral interventions such as teaching self-monitoring skills and promoting behavioral self-awareness, goal-setting, and problem-solving. Trials have demonstrated that taking behavioral theory into account, particularly social cognitive theory (self-monitoring and self-efficacy as key concepts) and CBT, leads to increased success in lifestyle modification interventions 15 …”
Section: Masldmentioning
confidence: 99%
“…Trials have demonstrated that taking behavioral theory into account, particularly social cognitive theory (selfmonitoring and self-efficacy as key concepts) and CBT, leads to increased success in lifestyle modification interventions. [15]…”
Section: Behavioral Change Strategiesmentioning
confidence: 99%
“…Despite the foreseeable advent of pharmacologic treatment aiming at resolution of steatohepatitis and regression of fibrosis, lifestyle interventions will remain the foundation of treatment of MASLD 3 . To increase awareness about diet and eating habits, behavioural therapy has been established as an important intervention to promote these lifestyle recommendations 4 . However, despite the positive results of lifestyle interventions in the short term, they remain challenging in clinical practice in the long term due to a lack of adherence and high attrition rates 5,6 …”
mentioning
confidence: 99%